Asymptomatic congenital malaria among neonates of mothers attending antenatal clinic in University of Medical Sciences Teaching Hospital, Akure - Oluwafemi, Rosena O.; Folarin, Bamidele J.; Bello, Emmanuel O.; Irinyenikan, Theresa A. (International Journal of Advances in Medicine, 2025)
Background: Congenital malaria can be a serious cause of morbidity and mortality in the neonates if not detected. Clinical features of congenital malaria are non-specific and could be confused with other forms of infections in the newborn. The study sets out to document presence of asymptomatic congenital malaria among neonates of mothers attending antenatal clinic in University of Medical Sciences Teaching Hospital, Akure. Methods: Mother-baby pairs were recruited into the study from the maternity section of the hospital, blood samples were taken from maternal peripheral blood, placental maternal side, cord blood and peripheral blood of the newborn babies and analyzed for presence of malaria parasite by microscopy methods. Data analyses were done using Statistical Package for the Social Sciences (SPSS) version 24.0 Results: Eighty-six (79.6%) of the babies were positive for malaria parasites, 59 (54.6%) of them were male children and 49(45.4%) were female. Fifty mothers (58.1%) had peripheral or placental parasitaemia. Babies of mothers who used long lasting insecticide treated nets (LLIN) and intermittent preventive therapy IPT-SP were significantly less infected while babies of first- and second-time mothers were significantly more infected. Majority of the babies 77/86 (89.5%) however had low intensity parasitaemia. Conclusions: Congenital malaria is no more a rare disease especially in endemic regions, prevention of mother-to-child transmission should be aggressively pursued.